Presentations of pulmonary embolism in COVID-19: An Indian case series - Daniel, Jefferson; Isaac, Barney; Balamugesh, Thangakunam; Nair, Avinash Anil; Christopher, Devasahayam Jesudas (Indian Journal of Case Reports, 2024)
The prevalence of pulmonary embolism (PE) among COVID-19 infections is significantly high. However, in resource-limited settings, appropriate computed tomography (CT) imaging is not possible for all COVID-19 patients. Very sick patients suspected of a PE may not be fit to be shifted to the CT room. Hence, it is likely that PE is underdiagnosed in Indian COVID-19 patients. Coexisting PE should be considered in all patients with influenza-like illnesses who have a Type 1 respiratory failure out of proportion to the severity of COVID- 19 radiology. In this case series, we discuss the different presentations of PE in patients with COVID-19.